2016
DOI: 10.1016/j.ajpath.2016.08.008
|View full text |Cite|
|
Sign up to set email alerts
|

BGP-15 Improves Aspects of the Dystrophic Pathology in mdx and dko Mice with Differing Efficacies in Heart and Skeletal Muscle

Abstract: Duchenne muscular dystrophy is a severe and progressive striated muscle wasting disorder that leads to premature death from respiratory and/or cardiac failure. We have previously shown that treatment of young dystrophic mdx and dystrophin/utrophin null (dko) mice with BGP-15, a coinducer of heat shock protein 72, ameliorated the dystrophic pathology. We therefore tested the hypothesis that later-stage BGP-15 treatment would similarly benefit older mdx and dko mice when the dystrophic pathology was already well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 50 publications
3
40
0
Order By: Relevance
“…They suggested that BGP-15's efficacy was mediated via membrane lipid therapy mechanisms (Salah et al, 2016), an effect that has also been established in other myopathies (Gehrig et al, 2012). Furthermore, BGP-15 has recently been shown to improve certain myopathological aspects of DMD such as collagen deposition (Kennedy et al, 2016), which is consistent with our data.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…They suggested that BGP-15's efficacy was mediated via membrane lipid therapy mechanisms (Salah et al, 2016), an effect that has also been established in other myopathies (Gehrig et al, 2012). Furthermore, BGP-15 has recently been shown to improve certain myopathological aspects of DMD such as collagen deposition (Kennedy et al, 2016), which is consistent with our data.…”
Section: Discussionsupporting
confidence: 92%
“…The cumulative OXA dosage used in our study is equivalent to that given to humans, scaled for the metabolic activity of mice according to Reagan-Shaw et al (2008). The concentrations and injection protocol for OXA have been used and published by our collaborators previously (Stojanovska et al, 2015; McQuade et al, 2016b), while the BGP-15 dosage administered has proven efficacious against murine myopathies (Chung et al, 2008; Gehrig et al, 2012; Kennedy et al, 2016). On day 14, mice were housed in the Promethion metabolic system for 24 h and on day 15, scanned again for changes in body composition, prior to being anaesthetized (sodium pentobarbitone, 60 mg/kg).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…BGP-15 is a hydroxylamine derivative that has been shown to exert cyto-and neuroprotective effects in mammalian models of injury, stress, and disease (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). These improvements in cellular function have been correlated with the activation of several intracellular pathways.…”
mentioning
confidence: 99%
“…These improvements in cellular function have been correlated with the activation of several intracellular pathways. For example, the heat-shock response is enhanced by increased levels of the molecular chaperone HSP72 (21,24,26,28,29), possibly mediated by Rac-1 signaling (31, 32). BGP-15 also decreases phospho-JNK (pJNK) and p38 stress signaling (21, 23) and increases AKT and IGFR1 protective signaling (23,25).…”
mentioning
confidence: 99%